Curriculum Construction of the Muhammadiyah and Salafi Education Systems: A Comparative Study of Islamic Education Systems in Indonesia - Ardiansyah, Ardiansyah (Abjadia : International Journal of Education, 2026)
This research analyzes the contestation of curriculum paradigms between the education system promoted by Persyarikatan Muhammadiyah and educational institutions based on the Salaf Manhaj. The three main objectives of this study are to describe the philosophy and construction of the curriculum, analyze the substantial differences in curriculum components, and identify the implications of the curriculum on student character and their responses to contemporary issues. The research findings indicate that the Muhammadiyah curriculum is rooted in modernistic integrative philosophy and the principle of ijtihad. This philosophy produces a balanced dual curriculum (religious sciences and general sciences) aimed at producing intellectual scholars (ulul albab) with a social transformation orientation. The Muhammadiyah curriculum uses critical rational methods (such as Project Based Learning) and focuses on contemporary jurisprudence. Conversely, the Salafi curriculum is based on a conservative purification philosophy and the principle of Ittiba' (absolute obedience). This resulted in a single, religiously dominated curriculum (80-90% of the material) aimed at producing students of knowledge oriented toward preserving doctrine. The method used is authoritative receptive (such as Talaqqi and memorization) with a focus on pure creed. The implication is that Muhammadiyah graduates demonstrate inclusive, adaptive, and proactive characteristics toward national policies, and possess global competitiveness. Meanwhile, Salafi graduates exhibit strong doctrinal characteristics but are at risk of being exclusive and reactive toward the adoption of a general curriculum. In summary, this contestation divides the Islamic education system in Indonesia between a model that prioritizes global relevance (Muhammadiyah) and a model that prioritizes doctrinal authenticity (Salafi).